Mobilization of fruit, small fruit and nut crop genetic resources in Belarus - Z. A. Kazlouskaya; L. V. Fralova; A. A. Taranau; V. A. Yakimovich; I. G. Palubiatka (Труды по прикладной ботанике, генетике и селекции)
Background. Natural populations of fruit and small fruit plants in Belarus and their specific and varietal composition for a long time attracted the attention of pomologists and breeders. Identification and mobilization of unique local forms and landraces as genetic sources of useful traits as well as monitoring duplicate collections will contribute to their more effective use in breeding practice to develop competitive domestic cultivars of various crops and reveal the adaptability of foreign cultivars to the conditions of Belarus.Methods. The itinerary of the collecting mission passed through 6 regions of the Republic of Belarus (Gomel, Minsk, Mogilev, Vitebsk, Brest, and Grodno) in 2012–2017.Results. As a result, 221 samples of fruit, small fruit and nut plants were collected, including 18 rootstocks of fruit crops. By 2021, 105 unique landraces were tested in the plant introduction and quarantine nursery and planted in the field gene bank, including 28 accessions of apple, 33 of pear, 11 of sour cherry, 5 of sweet cherry, 9 of plum, 8 of apricot, 1 of almond, 2 of hazel, 3 of garden strawberry, 1 of black chokeberry, 1 of viburnum, and 1 of bird cherry. There are plans to use the obtained accessions in breeding practice assources of valuable agronomic traits (high winter hardiness, high yield, resistance to a set of plant pathogens, etc.).